Anime, religion and spirituality profane and sacred worlds in contemporary Japan - Buljan, Katharine; Cusack, Carole M. 1962- (Equinox, 2015)
"The mutual imbrication of the profane and sacred worlds in anime, along with the profound reciprocal relationships between 'Eastern' (Japanese) and 'Western' (chiefly American) culture in the development of the anime artistic form, constitute the twin narrative arcs of the book. One of the most significant contributions of this book is the analysis of the employment of spiritual and religious motifs by directors. The reception of this content by fans is also examined."